Studi Fenomenologis: Dinamika Motivasi Atlet Bola Basket Pasca-Hiatus Dua Tahun - Arini Nurhayati Azizah Putri; Miftakhul Jannah (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to understand the motivational dynamics of a basketball athlete after a two-year hiatus due to injury. This research employed a qualitative approach with a phenomenological design. The participant was a 23-year-old basketball athlete who had been actively involved in basketball since the age of 12 and had experienced an injury that led to a hiatus. Data were collected through in-depth interviews and analyzed thematically. The findings show that the athlete's motivation after the hiatus was dynamic and influenced by love for basketball, injury experience, self-reflection, social support, family relationships, and athletic identity. The hiatus was not merely understood as a period of absence from sport, but also as a phase of recovery and reinterpreting the meaning of basketball. The participant returned to playing not only because of competitive demands, but because basketball had become an important part of life and self-identity. Keywords: Basketball, Sports Injury, Hiatus, Athlete Motivation, Sport Psychology